Pengaruh Edukasi Kesehatan Repruduksi Remaja Putri Terhadap Pengetahuan Tentang Personal Hygiene Saat Menstruasi di Universitas X - Anita Herawati; Linda Kusumawati (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
Adolescent girls are more at risk of having their reproductive organs infected. Reproductive tract infections are one of the causes of improper reproductive organ hygiene behavior. The solution is to provide reproductive health education about personal hygiene during menstruation so that knowledge increases for the betterTo identify the influence of reproductive health education on female teenagers regarding personal hygiene during menstruation at University X. This research method is pre-experimental with a one group pretest posttest design. The sampling technique was purposive sampling, samples were taken based on research criteria, a sample of 30 X students. Data analysis in this study used the marginal homogeneity test. esearch results, pretest 10 people (33.3%) were categorized as good, 10 people (33.3%) were categorized as sufficient and 10 people (33.3%) were categorized as poor. Posttest results, 24 people (80.0%) were categorized as good, 6 people (20.0%) were categorized as fair. The results of the marginal homogeneity test are p value = 0.0001 where p < 0.05 means there are differences between variables. Conclusion: There is an influence of reproductive health education on young women regarding personal hygiene during menstruation at University X.